Neurovascular bundle preservation in robotic-assisted radical prostatectomy: How I do it after 15.000 cases - Moschovas,Marcio Covas (2022)
ABSTRACT Despite the neuroanatomy knowledge of the prostate described initially in the 1980's and the robotic surgery advantages in terms of operative view magnification, potency outcomes following robotic-assisted radical prostatectomy still challenge surgeons and patients due to its multifactorial etiology. Recent studies performed in our center have described that, in addition to the surgical technique, some important factors are associated with erectile dysfunction (ED) following robotic-assisted radical prostatectomy (RARP). These include preoperative Sexual Health Inventory for Men (SHIM) score, age, preoperative Gleason score, and Charlson Comorbidity Index (CCI). After performing 15,000 cases, in this article we described our current Robotic-assisted Radical Prostatectomy technique with details and considerations regarding the optimal approach to neurovascular bundle preservation.